تجديد منهجية عرض التراث الديني عند الشيخ محمد الغزالي - Mohd Daud, Noor Amali (2019)
The paper investigates views of Shaikh Muhammad al-Ghazzali on turath, its importance, and the need to revitalize the methodology of presenting turath in the contemporary era. The study found that al-Ghazzali is in a mediating position between those who reject turath and those who succumb blindly to turath without any attempt to fit it to contemporary settings.